Nanorods with multidimensional optical information beyond the diffraction limit - Shihui Wen; Yongtao Liu; Fan Wang; Gungun Lin; Jiajia Zhou; Bingyang Shi; Yung Doug Suh; Dayong Jin (Nature Communications, 2020)
Development of functional nanostructures can enable a range of applications in imaging and nanoscale science. Here, the authors fabricate and characterize complex heterogeneous nanorods with diverse, tunable sub-wavelength structures.